Mental health in South Sudan: a ticking time bomb - Sieta Adhieu Majok (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Decades of war and conflict have caused a considerable amount of physical and mental trauma among South Sudanese. Mental health remains a heavily neglected, unacknowledged issue in South Sudan despite affecting all facets of society